Evaluation of Groundwater Quality for Drinking Purpose in the Noyyal River Basin, Tamil Nadu through Water Quality Index (WQI) and GIS Methods - R. Madhumitha; K. Kumaraswamy (National Geographical Journal of India, 2022)
Noyyal basin is one of the dynamic river basins in Tamil Nadu which is known for intensive agriculture and housing several industrial corridors. These activities significantly deteriorated the quality of surface and groundwater resources of the basin. The groundwater quality is analysed based on its physical and chemical parameters. The physical parameters of Potential of Hydrogen (pH), Electrical Conductivity (EC), Total Dissolved Salts (TDS), and Total Hardness (TH) were analysed.Chemical parameters were assessed based on the major cations of Calcium (Ca), Magnesium (Mg), Sodium (Na), Potassium (K), and anions of Chloride (Cl), Sulphate (SO4), Nitrate (NO3) and Bi-carbonate (HCO3). These parameters were then compared with the standards of the World Health Organisation (WHO) and the Bureau of Indian Standards (BIS) for drinking purposes. Geographic Information System (GIS) was utilised to generate the spatial distribution of the selected parameters. These layers were overlaid to achieve the overall water quality index for drinking purposes. The results reveal that as much as 37 per cent of the study area experiences higher water quality index, 40 per cent under moderate and 23 per cent has a poor index for drinking purpose. Spatially, the western parts of the basin show high quality and the central and eastern portion shows moderate to poor quality.